1992
DOI: 10.1128/jb.174.11.3651-3658.1992
|View full text |Cite
|
Sign up to set email alerts
|

Sequence and transcriptional analysis of the Streptomyces glaucescens tcmAR tetracenomycin C resistance and repressor gene loci

Abstract: Sequence analysis of the tcmA tetracenomycin C resistance gene from Streptomyces glaucescens GLA.O (ETH 22794) identifies one large open reading frame whose deduced product has sequence similarity to the mmr methylenomycin resistance gene from Streptomyces coelicolor, the Streptomyces rimosus tet347 (otrB) tetracycline resistance gene, and the atr1 aminotriazole resistance gene from Saccharomyces cerevisiae. These genes are thought to encode proteins that act as metabolite export pumps powered by transmembrane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
65
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(68 citation statements)
references
References 48 publications
(41 reference statements)
3
65
0
Order By: Relevance
“…The highest levels of similarity, extending over the complete sequence, existed with presumptive transmembrane proteins from antibiotic-producing Streptornyces, including LmrA from S. lincolnensis [6], TcmA from S. glaucescens [4] and Mmr from S. coelicolor [S], which confer resistance to lincomycin, tetracenomycin C and methylenomycin, respectively (Figs 4 and 5). In addition, a significant level of similarity was found with QacA, which confers resistance to a variety of antiseptic and desinfectant agents in Staphylococcus uureus [33] and for two proteins from S. coelicolor, ActII-ORF2 and ActV-ORF1, which appear to be implicated in the efflux of actinorhodin [2, …”
Section: Comparison Of Pur8 With Several Transporter Proteinsmentioning
confidence: 99%
“…The highest levels of similarity, extending over the complete sequence, existed with presumptive transmembrane proteins from antibiotic-producing Streptornyces, including LmrA from S. lincolnensis [6], TcmA from S. glaucescens [4] and Mmr from S. coelicolor [S], which confer resistance to lincomycin, tetracenomycin C and methylenomycin, respectively (Figs 4 and 5). In addition, a significant level of similarity was found with QacA, which confers resistance to a variety of antiseptic and desinfectant agents in Staphylococcus uureus [33] and for two proteins from S. coelicolor, ActII-ORF2 and ActV-ORF1, which appear to be implicated in the efflux of actinorhodin [2, …”
Section: Comparison Of Pur8 With Several Transporter Proteinsmentioning
confidence: 99%
“…PhlE also has structural similarity with integral membrane proteins associated with resistance which are encoded within clusters responsible for polyketide biosynthesis (Brautaset et al, 2000;Fernandez-Moreno et al, 1991;Guillfoile & Hutchinson, 1992;Marger & Saier, 1993;Molnar et al, 2000). It has been reported that phlE mutants produce less PHL than the parent strain (Bangera & Thomashow, 1996.…”
Section: Introductionmentioning
confidence: 99%
“…The phlE gene, located at the 39 end of the phlACBD operon in P. fluorescens strains (Bangera & Thomashow, 1996Delany, 1999) encodes a putative transmembrane permease with 12 predicted transmembrane segments (TMS) (Bangera & Thomashow, 1999 transporter mediating resistance to a range of structurally dissimilar drugs (Paulsen & Sukurray, 1993;Yoshida et al, 1990). PhlE also has structural similarity with integral membrane proteins associated with resistance which are encoded within clusters responsible for polyketide biosynthesis (Brautaset et al, 2000; Fernandez-Moreno et al, 1991;Guillfoile & Hutchinson, 1992;Marger & Saier, 1993;Molnar et al, 2000). It has been reported that phlE mutants produce less PHL than the parent strain (Bangera & Thomashow, 1996.…”
mentioning
confidence: 99%
“…13 Meanwhile, RapH, RapG and RapY have been shown to contain a helix-turn-helix motif for DNA binding. 13 Although RapY exhibits sequence similarity to repressors of antibiotic export such as ActII from actinorhodin 58 and TcmR from tetracenomycin gene clusters, 59 the sequences of RapG are similar to those of the positive regulatory proteins SoxS and Rob from E. coli. 13 The N-terminal region of RapH contains a potential ATP-binding motif matching the canonical P-loop consensus.…”
Section: Biological Activities Of Rapamycin and Its Analogsmentioning
confidence: 99%